Liberalization of foreign direct investment in Latin America: a brief comparative approach of Brazil, Peru and the Andean Group - Alcalde C., Javier (Universidad del Pacífico, 1997)
This article addresses the significance of the recent global trend toward liberalization of foreign direct investment (FDI), showing the importance of Latin America in the process and analyzing the regulation of FDI in three countries (Brazil, Chile, and Peru) and one integration movement (the Andean Group) of the region. The evolution of these four FDI regimes, from the 1970s to 1996, reflects the great changes in economic policy that have taken place in Latin America.   After presenting some theoretical background concerning levels of FDI regulation in the world economy, the main aspects of the national regulation of FDI, and traditional conflict issues between multinational enterprises and host governments, the author proceeds to outline, on the one hand, the rise and fall of economic nationalism in Latin America (between 1970 and the mid-1980s), and, on the other, the central tenets of the so-called "Washington Consensus" (among the U.S. government, the International Monetary Fund, and the World Bank), which guide the liberalization of FDI in the 1990s.   The article describes and analyzes the evolution of the four FDI regimes comparing them among themselves as well as with the World Bank Guidelines on FDI and NAFTA investment provisions, in order to establish their degree of convergence with the liberal rules supported by capital-exporting nations.